2020
DOI: 10.18231/j.ijce.2020.024
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of post-operative pain with different calcium hydroxide formulations when used as intracanal medicament in root canal treatment- In vivo study

Abstract: The purpose of this study was to compare to evaluate the post operative pain with different calcium hydroxide formulations when used as intracanal medicament in root canal which was evaluated by VAS scale. The 150 subjects were randomly assigned to four groups and one control group depending upon the intracanal medicament: Group 1: Calcium hydroxide paste (Ivoclar) was used as intracanal medicament, Group 2: Calcium hydroxide paste with iodoform (Metapex) was used as intracanal medicament, Group 3: Calcium hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…A recent study compared the effects of chitosan (natural polysaccharide) and metapex (silicone oil-based vehicle containing iodoform) to Ca(OH) 2 paste—a polyethylene glycol paste (viscous) as a vehicle and found that it reduced postoperative pain to some extent, indicating its potential for use as a vehicle to aid in pain management [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study compared the effects of chitosan (natural polysaccharide) and metapex (silicone oil-based vehicle containing iodoform) to Ca(OH) 2 paste—a polyethylene glycol paste (viscous) as a vehicle and found that it reduced postoperative pain to some extent, indicating its potential for use as a vehicle to aid in pain management [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Four studies [ 26 27 31 32 ] used the VAS, one study [ 29 ] used the HP VAS, and another [ 30 ] used the NRS. One study [ 28 ] used the universal pain assessment tool, whereas three studies [ 4 8 15 ] used the verbal rating scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation